Design, Performance and Testing of a Quad Rotor Biplane Micro Air Vehicle for Multi Role Missions. Issue 3 (September 2014) - Hrishikeshavan, Vikram; Bogdanowicz, Christopher; Chopra, Inderjit
It is useful to combine hover and forward flight capability of air vehicles into a hybrid design. This paper discusses the development of one such hybrid air vehicle: Quadrotor biplane. The proof-of-concept vehicle weighs 240 grams and consists of four propellers with wings arranged in a biplane configuration. The performance of the propeller-wing was investigated in non-axial flow conditions through a systematic series of wind tunnel experiments. The effect of the wing on propeller slipstream and vice versa significantly changed the magnitude of vertical and horizontal forces when compared with the forces produced by an isolated propeller. Accounting for these effects, trim analysis showed that the maximum speed of 11 m/s at 0 deg shaft angle and a cruise speed of 4 m/s at 18 deg shaft angle was achievable. The cruise power was approximately one-third of that required for hover. Free flight testing of the proof-of-concept vehicle successfully showed feasibility of vehicle to achieve equilibrium transition flight. In order to improve performance, a few key design parameters such as airfoil profile, wing aspect ratio, biplane wing spacing and offset between propeller axis and wing chord were also experimentally investigated. It was found that a careful trade-off between efficiency and compactness affects the final choice of the design.